The dipeptidylpeptidase‐IV inhibitors sitagliptin, vildagliptin and saxagliptin do not impair innate and adaptive immune responses. Issue 6 (29th December 2013) - Anz, D.; Kruger, S.; Haubner, S.; Rapp, M.; Bourquin, C.; Endres, S.
Abstract Inhibitors of dipeptidylpeptidase IV (DPP‐IV) represent a novel class of frequently used anti‐diabetic drugs. In addition to its function in metabolic regulation, DPP‐IV also plays a role in the immune system. Whether the DPP‐IV inhibitors sitagliptin, vildagliptin or saxagliptin impair immune responses is, however, currently unknown. Here, we investigated the effect of these agents on both innate and adaptive immunity. We found that the DPP‐IV inhibitors did not affect the innate immune response induced by Toll‐like receptor (TLR) ligands, as cytokine secretion and induction of co‐stimulatory molecules by human blood mononuclear cells was not impaired. Furthermore, proliferation of T cells and suppressive function of regulatory T cells was preserved. Mice treated with vildagliptin showed normal cytokine production, immune cell activation and lymphocyte trafficking upon TLR activation. Thus, crucial immunological parameters remain unaffected upon treatment with DPP‐IV inhibitors, a fact that is reassuring with respect to safety of these drugs.